The value of HB in conjoint/choice analysis - Orme, Bryan K. (Henry Stewart Talks, 2010)
Introduction to conjoint/choice analysis, How HB has improved ratings-based conjoint methods, Why HB has particularly benefited choice-based models, Market simulation issues including IIA, Practical considerations such as utility constraints and using proper priors